The Territory of Japan Its History and Legal Basis - Serita, Kentaro (Open Access e-Books, 2023)
This Open Access book carefully examines the legal and historical bases of the territory of Japan as a modern State from the Meiji period to 2002. A new preface summarizes key developments in the situation up through 2022. Japan's current territory is stipulated by the Potsdam Declaration (1945) and the Treaty of Peace with Japan (1951); it includes the Northern Territories, the Senkaku Islands, and Takeshima. Japan has demanded the return of the Northern Territories, comprising the islands of Etorofu, Kunashiri, Shikotan and Habomai, which are occupied by Russia. China has claimed sovereignty over the Senkaku Islands, which are validly controlled by Japan; Japan has claimed sovereignty over Takeshima, which is occupied by the Republic of Korea. This book analyzes the current status of these territorial topics, drawing on historical documents and international legal precedent, and it suggests peaceful methods to address them. In discussing territorial land, sea, and air space, this work touches upon postwar concepts defining modern international law and relevant rules on these subjects-exclusive economic zones (EEZs), continental shelves, and air defense identification zones (ADIZs)-found in international treaties, such as the United Nations Convention on the Law of the Sea (UNCLOS), and related domestic laws. Kentaro Serita is Professor Emeritus of Kobe University, Japan.--